Caching efficiency of information‐centric networking. Issue 2 (1st June 2013) - Liu, Wai‐Xi; Yu, Shun‐Zheng; Gao, Ying; Wu, Wei‐Tao
Abstract : In‐network caching leveraged in information‐centric networking (ICN) is one key difference between ICN and the current Internet. Taken into account the complexity and practicality of technology, cooperatively in‐network caching is yet so far. However, caching efficiency of current uncooperative caching scheme is disappointing. Network coding is considered as the most promising information theoretic approach to improve performance in current Internet. The authors' previous work has proposed information‐centric networking built network coding (ICN‐NC). In this study, the authors will prove that ICN‐NC can also improve caching efficiency besides network performance. First, a theoretical model is proposed to evaluate caching efficiency of ICN and ICN‐NC, and compare the caching efficiency between ICN and ICN‐NC both analytically and by simulations. Then effect of different parameters on caching efficiency, such as file size, copy size and probability of replacement etc., are also extensively researched. Furthermore, the authors formulate the overall caching efficiency as a multi‐objective optimisation problem with constraints, and then Pareto optimal set to achieve an optimal allocation of network‐wide caching is obtained.